Influence of myocardial scar on the response to frequent premature ventricular complex ablation. Issue 5 (21st September 2018) - Penela, Diego; Martínez, Mikel; Fernández-Armenta, Juan; Aguinaga, Luis; Tercedor, Luis; Ordóñez, Augusto; Acosta, Juan; Martí-Almor, Julio; Bisbal, Felipe; Rossi, Luca; Borràs, Roger; Linhart, Markus; et al.
Abstract : Objective: This study aims to evaluate the influence of myocardial scar after premature ventricular complexes (PVC) ablation in patients with left ventricular (LV) dysfunction. Methods: 70 consecutive patients (58±11 years, 58 (83%) men, 23% (18–32) mean PVC burden) with LV dysfunction and frequent PVCs submitted for ablation were included. A late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) was performed prior to the ablation and a quantitative and qualitative analysis of the scar was done. Results: Left ventricular ejection fraction progressively improved from 34.3%±9% at baseline to 44.4%±12% at 12 months (p<0.01) and 48 (69%) patients were echocardiographic responders. New York Heart Association class improved from 1.96±0.9 points at baseline to 1.36±0.6 at 12 months (p<0.001). Brain natriuretic peptide decreased from 120 (60–284) to 46 (23–81) pg/mL (p=0.04). Twenty-nine (41%) patients showed scar in the preprocedural LGE-CMR with a mean scar mass of 10.4 (5–20) g. Mean scar mass was significantly smaller in responders than in non-responders (0 (0–4.7) g vs 2 (0–14) g, respectively, p=0.017). PVC burden reduction (OR 1.09 (1.01–1.16), p=0.02) and scar mass (OR 0.9 (0.81–0.99), p=0.04) were independent predictors of response, but the former showed a higher accuracy. Conclusions: Presence of myocardial scar modulates, but does not preclude, the probability of response to PVC ablation in patients with LV dysfunction.